PENERAPAN PEMBELAJARAN KOOPERATIF TPS DENGAN PENDEKATAN OPEN ENDED UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Wati, Krisdia (Program Studi Pendidikan Matematika FTIK IAIN Langsa, 2019)
This research is based on the low level of creative thinking of the students, this is because in the current study it is felt that the teacher is still less creative in composing the problem, why can be said so because the teacher only gives convergent problem where there is only one correct answer. One alternative to overcome this with teachers should provide a devergen problem by applying the model of learning Think Pair and Share with Open ended approach. The aim of this research is to know and to describe 1) to describe the improvement of students' mathematical thinking ability to construct flat rectangle, 2) to know the student's response to the use of Cooperative TPS learning model with Open-Ended approach on rectangular material. This research includes classroom action research. Location of research in SMP N 2 Widang with subject of student of class VII-E counted 25 student. Instruments in this research is a test of students' creative thinking ability and student response questionnaire. The result of the creative thinking test is obtained after applying the think pair share model with the open ended approach shows that the students' mathematical creative thinking ability has increased on each indicator, the average of creative thinking ability each cycle has increased, because from the initial average of 0.3 in cycle I, increased to 12.4 in cycle II, and in cycle III also increased by 16, and student response to use of Think Pair Share learning model with Open ended approach proved quite effective, efficient, and student responded positively when learning process take place. This is indicated by the results of the study average percentage of student response 99% because greater than 75% and who respond negatively as much as 1% then it can be said positive response